Efektivitas Relaxing Breathing Exercise Terhadap Kualitas Tidur dan Kontrol Kadar Gula Darah Pada Pasien Diabetes Melitus Kronik: Tinjauan Literatur - Jesus, Dionencia Nahak De; Prabawati, Dewi (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2025)
Background: This literature review study is motivated by the phenomenon of insomnia in patients with diabetes mellitus which is getting more serious over time and has an impact on sleep quality. Relaxation techniques are needed, namely relaxing breathing exercises, which can affect sleep quality and can cause endocrine and metabolic disorders such as glucose tolerance disorders, insulin resistance and reduced response to insulin. Objective: to see the effectiveness of relaxing breathing exercises on sleep quality in patients with diabetes mellitus. Method: A literature review was conducted on seven articles obtained from three databases, Proquest, Google Scholar and Pubmed. The keywords for searching articles are